ЭХОСТРУКТУРНЫЕ ИЗМЕНЕНИЯ ПРИ УЛЬТРАЗВУКОВОМ ИССЛЕДОВАНИИ БРАХИОЦЕФАЛЬНЫХ АРТЕРИЙ У БОЛЬНЫХ РЕВМАТОИДНЫМ АРТРИТОМ - О. Ю. Чураков; Н. П. Шилкина (SINAPS LLC, 2014)
Of 125 patients included in the study 70 had rheumatoid arthritis (RA). They were compared to 40 patients with deforming osteoarthritis (DOA) and 15 patients with atherosclerosis of great cerebral arteries (MCA). Control group consisted of 40 persons having remission randomized according to age and sex. Carotid, vertebral arteries and cerebral circulation were investigated with ultrasound duplex scanning on the unit «Vingmed system 5» (Norway, 2002). Duplex scanning in RA patients in comparison with control group and OA patients showed the increase of the stenotic lesions of the carotid and the vertebral arteries which is more evident in group by seropositive RA and in RA patients with extra-articular manifestations. Significant data were received when studying the carotid deformation. Comparison of the RA groups showed considerable differences: in RA group with systemic manifestations increase of the sinuation rate became evident both in common carotid arteries (χ2 = 1,76; NA), and in internal carotid arteries (χ2 = 8,44; p = 0,01). Data received in present study indicate that in RA patients changes of cardiovascular system, characterized by forwardness of the atherosclerosis, take place. Evidence of the atherosclerotic changes associates with presence of RA systemic manifestations, high inflammatory process activity and seropositivity by rheumatoid factor.